Primacy and Nationalism - Зизијулас, Јован (Sabornost - The Theological Year-book, 2012)
The main issue that the author raises here is whether it is mandatory, and how can the Orthodox Church function primarily with the given existence of nationalism? How does the issue of ecclesiology and nationalism work at first in the Orthodox Church, in what sense as well as practically? To answer these questions the author first describes the basic theological, ecclesiological principles, on which the development took primacy issues in the Orthodox Church. Finally, he answers the question of whether, and how nationalism may survive in the postmodern era, that might be the importance of primacy and ecclesiology, which was introduced in the new state of affairs.